’Creative accounting’ in the Spanish professional football League: An attempt to dodge the rules economic control? - Rudemarlyn Urdaneta Camacho; Juan Carlos Guevara Pérez; Emilio Martín Vallespín; Fernando Llena Macarulla (Revista de Contabilidad: Spanish Accounting Review)
Over the past decade, many studies have analysed the contribution of UEFA's Financial Fair Play (FFP) regulations and the Reglamento de Control Económico (RCE) of the Spanish Football League (LFP) to the financial sustainability of clubs. However, compliance with the regulations may create incentives to adopt accounting practices that seek to "dress up" the financial statements of clubs, deviating from the main objective of presenting a true and fair view of the entity. This study analyses the financial and non-financial factors that lead to earnings management practices in Spanish professional football, to identify the impact that the implementation of the LFP RCE has had on the quality of accounting information. Given the importance of intangible assets in the football industry, as they represent the rights paid for the transfer of players, the study uses Key's (1997) model to consider this item to obtain discretionary accrual adjustments. Subsequently, panel data (FGLS) allows us to identify possible relationships between these adjustments and financial and non-financial variables. The results show that smaller and more leveraged first division clubs are more prone to manipulate their accounting information after the introduction of RCE. In contrast to previous studies focusing on large teams, the present study provides a comprehensive analysis of one of the most popular European leagues (the Spanish league), considering clubs of different sizes. In addition, the study opens a debate on the appropriateness of specific accounting parameters in the football industry, such as the treatment of intangible assets related to player rights, which are one of the main items used by clubs to implement earnings management practices.